Geotechnical and geochemical appraisal of IFON clay, Southwestern Nigeria: Implications for industrial utilization - O, Ademila; T. H. T, Ogunribido; J. M, Abidoye (International Journal of Physical Research, 2019)
Clays are geological materials of economic potential in the manufacturing and environmental industries. Geotechnical properties and geochemical composition of Ifon clay deposits in Ondo State, Nigeria were investigated with the aim of determining their economic potentials. The geotechnical investigation includes consistency limits, strength, permeability and firing tests, while, X-ray fluorescence (XRF) method was used for determination of the bulk elemental composition of the clays using standard techniques. Geotechnical appraisal of the clay deposits revealed that high proportion of clay size fractions (52.3 – 66.1%) makes the clays suitable in their natural state for industrial raw materials. Activity of the clays was found to be low at approximately 0.3 – 0.7 and classified as inactive clays. Unconfined compressive strength varies between 3.4 N/mm2 and 4.7 N/mm2 and moderate shrinkage values (≤ 12%) indicate that the clays could be used as building construction materials. Coefficient of permeability of 7.75 × 10-8 to 1.72 × 10-5 cm/sec described the clays as low to impermeable soils suitable as barrier soils. SiO2 (64.41 – 68.74%) and Al2O3 (22.98 – 28.45%) contents dominate the clay geochemistry followed by iron oxide, Fe2O3 (3.57 – 8.31%) content among other oxides in traces, imply that they originated from underlying basement rocks subjected to varying degree of weathering. Low MgO, CaO, K2O and Na2O indicate no expandable clay minerals in the clays. The clays show low heavy metal concentrations which guarantee their suitability as raw materials in chemical industries. Thus, Ifon clay deposits are suitable for the production of ceramics, refractory bricks, paper, paints, rubber and fertilizer.